Penerapan Food Traffic Light sebagai Panduan Pemilihan Makanan Sehat di Kantin Fakultas Farmasi Universitas Gadjah Mada (Berita Kedokteran Masyarakat (BKM), 2020)
Purpose: Unhealthy eating patterns affect health status, even increasing the risk of non-communicable diseases. Health Promoting University is a holistic and comprehensive form of health intervention, such as policies implementation to supports healthy campus. This study aimed to know the changed of students attitudes towards healthy eating patterns with food traffic light to reduce the risk of non-communicable diseases. Method: This study used a quasi-experimental method with pre and post test group designed. Total sample in this study amounted 42 students that were given education with banners, leaflets, x-banner and food traffic light stickers in the canteen. Data onto attitudes towards eating patternss were obtained through filling out questionnaires before and after the intervention was carried out. Statistical tests used paired t-test. Result: Characteristics of respondents were mostly female (76%) and 20 years old (77%). P-value of the paired t-test 0.12 (p> 0.05) showed unsignificant results, with an average reduction from 55.7 to 54.7. The increase in post test scores occurred only 35.7% of respondents. There were no increase in attitude towards healthy eating patterns in college students. This happened because the distance between the spread of the media and the measurement was too close. The construction of the building caused some changed of the lecture activities and location, there by affecting the reach of media. Conclusion: There were no increased in attitude towards healthy eating patterns students after intervention. The spread of digital media through official accounts of student organizations are expected to broaden the range of given interventions